Reflections on the REDCo project - Weisse, Wolfram (British journal of religious education, 2011)
The REDCo project addressed the question of how study of religions and values in schools could contribute to either dialogue or tension in Europe. Researchers in the humanities and social sciences co-operated in order to gain better insight into how European citizens of different religious, cultural and political backgrounds could enter into dialogue which respected freedom of religion or belief. Empirical studies, targeting students in the 14- to 16-year age group, included a dual perspective of, on the one hand, the subjects' own perspectives and, on the other hand, analyses of examples of observed teaching. The project was funded by the European Commission for the period from March 2006 to March 2009 and was co-ordinated by the University of Hamburg. Eight European countries (Estonia, Russia, Norway, Germany, the Netherlands, France, England and Spain) participated. This contribution, by the project co-ordinator, provides an overview of the project and presents a personal evaluation.